Research progress and prospect in wire arc additive manufacturing magnesium alloy - LIU Hongjie; LIU Wencai; SUN Jiawei; WANG Xiyao; KUANG Siyu; WU Guohua (Cailiao gongcheng, 2024)
Wire arc additive manufacturing (WAAM) has received extensive attention from researchers due to its high deposition rate, high material utilization, low cost, and ability to manufacture large-scale components. It is expected to be widely used in rapid forming of magnesium alloys. The current types and requirements of wires used in WAAM of magnesium alloy were summarized. Then, the current preparation methods suitable for WAAM of magnesium alloy were introduced. The manufacturing technology, deposition mechanism, microstructure and mechanical property of various WAAM-processed magnesium alloys were discussed. Finally, the problems such as the few types of available wires and the uncontrollable shape and property of components for wire arc additive manufacturing of magnesium alloys were analyzed. The optimization of properties and application of components for wire arc additive manufacturing of magnesium alloys were forecasted.